2014
DOI: 10.1111/rda.12335
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Isoflavones on Androgens and Glucocorticoids During Puberty on Male Wistar Rats

Abstract: Isoflavones are the most common phytoestrogens found in human diets. However, it is still not clear whether isoflavones have effects on the reproductive and the endocrine systems under normal dietary intake and overdose. The aim of this study was to determine how the most important isoflavones, genistein and daidzein, affect androgen and glucorticoid levels on male prepuberal rats. A hundred and seventy-five 30-day-old male Wistar rats were dosed orally by stomach tube every day for 35 days, with saline soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(77 reference statements)
3
11
0
Order By: Relevance
“…In this study, testicular androgen production on low doses of isoflavones groups resulted in a significant increase of T testicular levels, and a significant increase in DHT testicular levels. These findings are related to the serum androgen levels found in these animals previously reported by our group and confirm the onset of puberty at that delayed stage compare to control group at a hormonal and histological levels, as it was also reported that rats administered with high and low doses of isoflavones presented lower content of spermatozoa than control group (Caceres et al, ). On high doses of isoflavones group, T and A4 testes homogenates levels were significantly lower than control group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, testicular androgen production on low doses of isoflavones groups resulted in a significant increase of T testicular levels, and a significant increase in DHT testicular levels. These findings are related to the serum androgen levels found in these animals previously reported by our group and confirm the onset of puberty at that delayed stage compare to control group at a hormonal and histological levels, as it was also reported that rats administered with high and low doses of isoflavones presented lower content of spermatozoa than control group (Caceres et al, ). On high doses of isoflavones group, T and A4 testes homogenates levels were significantly lower than control group.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, exposure to low and high doses of isoflavones resulted in an alteration on the secretion of these hormones. This could be due to a delay on the onset of puberty previously reported (Caceres et al, ). On high‐dose groups LH levels did not increase until fifth week and FSH levels were higher during all the experiment.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Soybean phytoestrogens, in high and low dosages, have been reported to reduce testosterone serum concentrations (Weber et al 2001, Caceres et al 2014. Wisniewski et al (2003) stated that reduced testosterone biosynthesis can affect the reproductive physiology and behavior of phytoestrogen-fed rats.…”
Section: Histomorphometry Of Seminiferous Tubules and Sertoli Cell Countmentioning
confidence: 99%